2021
DOI: 10.1101/2021.03.24.436739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A polyyne toxin produced by an antagonistic bacterium blinds and lyses a green microalga

Abstract: Microalgae are key contributors to global carbon fixation and the basis of many food webs. In nature, their growth is often supported or suppressed by other microorganisms. The bacterium Pseudomonas protegens Pf-5 arrests the growth of the green alga Chlamydomonas reinhardtii, deflagellates the alga by the cyclic lipopeptide orfamide A, and alters its morphology. Using a combination of Raman microspectroscopy, genome mining and mutational analysis, we discovered a novel polyyne toxin we name protegencin that i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The initial functional assessment of cayG was based on a single crossover, which may lead to polar effects [4] . Thus, for the targeted gene deletion (approach a), we employed an improved method in which we replaced the target gene with an apramycin resistance cassette by double‐crossover knock‐in [9b] (Figure S1). As expected, the resulting cayG null mutant strain produces 2 in lieu of 1 (Figure 2A, trace b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial functional assessment of cayG was based on a single crossover, which may lead to polar effects [4] . Thus, for the targeted gene deletion (approach a), we employed an improved method in which we replaced the target gene with an apramycin resistance cassette by double‐crossover knock‐in [9b] (Figure S1). As expected, the resulting cayG null mutant strain produces 2 in lieu of 1 (Figure 2A, trace b).…”
Section: Resultsmentioning
confidence: 99%
“…Protegencin F ( 11 ) has a secondary alcohol in lieu of the terminal alkyne and may be regarded as a shunt product of the multiple chain desaturations [4] . We also synthesized the CuAAC ( 12 ) [9b] and the phosphopantetheinyl‐mimicking N ‐acetyl‐cysteamine thioester (SNAC) [17] ( 13 ) derivatives of 2 (Figure S39–S43) to probe the substrate requirements of CayG.…”
Section: Resultsmentioning
confidence: 99%
“…Mapping the diversity of polyyne biosynthetic gene clusters through functional gene and protein phylogenies permitted the discovery of an uncharacterized Pseudomonas polyyne BGC, pgn , and metabolite, protegencin. Hotter et al ( 22 ) have recently demonstrated that this P. protegens polyyne, protegencin, acts as an algicidal toxin of the green alga Chlamydomonas reinhardtii . In parallel to these studies characterizing protegencin, Murata et al ( 23 ) identified the same polyyne biosynthetic gene cluster in the biocontrol strain P. protegens Cab57, designating the molecules produced as protegenins.…”
Section: Discussionmentioning
confidence: 99%
“…protegenin [5] ) from Pseudomonas protegens [6] (Figure 1A). Their versatile ecological functions in protective symbioses [1b,4b] and their involvement in plant/algal, [6b] and mushroom [7] diseases have prompted the analyses of bacterial polyyne biosynthetic gene clusters (BGCs) [6a] . These BGCs harbor conserved core genes coding for a fatty acyl‐AMP ligase, three desaturases, an acyl carrier protein (ACP), a thioesterase, and an electron transport component such as rubredoxin (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high potential for bioprospecting, [9] as antifungals, [10] and for bio‐orthogonal chemistry [11] and in vivo imaging [6b,7] there is high interest in understanding the biochemical basis for microbial alkyne and polyyne formation. Although various in silico and genetic analyses have been performed, [1b,3,5,6,8a,9] bacterial polyyne fatty acid biosynthesis is still little understood.…”
Section: Introductionmentioning
confidence: 99%